Insights Beyond Numbers: Composite Indexing as a Lens to Illuminating the Nutritional Status of Karnataka - Kishore SG; Prashant Sajjan; Ramakrishna Reddy N; Ranganath TS (RGUHS National Journal of Public Health)
Introduction Adequate nutrition in a childrsquos life provides the essential building blocks for brain development healthy growth and a strong immune system and prevents non-communicable diseases associated with being overweight. Several data sources and studies indicate that the nutritional status of children continues to vary significantly across various districts in Karnataka. This study developed a nutritional index to measure and compare these differences.Methods A comprehensive nutritional index covering thirty districts of Karnataka has been developed using twelve key nutrition-related factors. For every district each indicatorrsquos scaled value was computed. Thus a composite nutritional index was calculated using the scaled values.Results Based on the final composite score the districts were ranked to reflect their nutritional status. Mandya topped the list of 30 major districts followed by Chitradurga and Ramnagara in second and third place respectively. Gadag received the lowest ranking followed by Yadagir and Bagalkot in second and third place and the districts in the Kalyana Karnataka region had lower nutrition indices.Conclusion The study delivered a composite index combining all 30 districts onto a single framework providing a fair visualization for assessing the current situation. Under multiple programmes Integrated Child Development Service ICDS has been objectively driven into mission mode. These schemes place a strong emphasis on convergence targeted approaches and the use of technology. In addition nutritional programmes should consider and address other factors such as place of residence illiteracy household income maternal malnutrition birth order poor sanitation illnesses and infections.